2012
DOI: 10.1088/1748-9326/7/2/024021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of institutional changes on land use: agricultural land abandonment during the transition from state-command to market-driven economies in post-Soviet Eastern Europe

Abstract: Environ. Res. Lett. 7 (2012) 024021A V Prishchepov et al land-use change offers vast opportunities for carbon balance and biodiversity, and for increasing agricultural production on previously cultivated lands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
142
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(159 citation statements)
references
References 56 publications
9
142
0
8
Order By: Relevance
“…For instance, the farmland abandonment rate of 18% detected with a MODIS time series has been observed during 2006-2008 across Russia, Poland, Belarus, Estonia, Latvia, Lithuania and the Ukraine [29]. While the direct comparison of land abandonment rates and patterns with other case studies across former Soviet Union is challenging because the time periods and abandonment definitions used vary among studies, the cross-border comparison in the ASB area revealed some interesting patterns, similar to cross-border studies in Eastern Europe [119,120]. For instance, our study revealed drastic differences in land abandonment rates among the neighboring countries (i.e., 4% in Kyrgyzstan and 33% in Kazakhstan) compared to variations in land abandonment rates at the province level within the studied countries.…”
Section: Discussionmentioning
confidence: 60%
“…For instance, the farmland abandonment rate of 18% detected with a MODIS time series has been observed during 2006-2008 across Russia, Poland, Belarus, Estonia, Latvia, Lithuania and the Ukraine [29]. While the direct comparison of land abandonment rates and patterns with other case studies across former Soviet Union is challenging because the time periods and abandonment definitions used vary among studies, the cross-border comparison in the ASB area revealed some interesting patterns, similar to cross-border studies in Eastern Europe [119,120]. For instance, our study revealed drastic differences in land abandonment rates among the neighboring countries (i.e., 4% in Kyrgyzstan and 33% in Kazakhstan) compared to variations in land abandonment rates at the province level within the studied countries.…”
Section: Discussionmentioning
confidence: 60%
“…These key questions are still largely unresolved and require models able to integrate plant physiology, demography, and biogeography, as well as social and land-use sciences. A key future challenge is to better account for human decision-making, policy impacts, and feedbacks in models and projections of future vegetation change (140).…”
Section: Summary and Future Challengesmentioning
confidence: 99%
“…Similarly in Europe, where agricultural land is assumed to be partially turned into forest land as well (Rounsevell et al 2006;Stoate et al 2009;Ruskule et al 2016). An increase in forest land area and a decrease in farmland area has been observed in Europe since the early 19 th century (Wulf 2004;Prishchepov 2012); currently, an area of approximately 12 -16 million hectares (FAO 2008;Campbell et al 2008) is considered to be afforested on this continent. The area of agricultural and non-forest land suitable for afforestation can be illustrated on the example of the Czech Republic.…”
Section: Statistical Evaluationmentioning
confidence: 99%